Effect of Service Period, Gestation Period and Dry Period on Milk Production Traits in Kankrej Cattle - Pareek, Nawal Kishor; Ankuya, K.J.; Patel, M.P.; Rathod, B.S.; Prajapati , K.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present investigation was undertaken to study the effect of non-genetic factors, viz., service  period (SP), dry period (DP) and gestation period (GP) on various milk production traits in Kankrej  cattle. 1235 lactation records (2nd-7th ) of 475 Kankrej cows, progeny of 75 bulls that were maintained  at University Livestock Research Station, Sardarkrushinagar (Gujarat), calved during 1980-2014,  were studied. The effects of service period (111.64 ± 52.55 days) and dry period (143.17±28.78  days) on total lactation milk yield (2089.45±582.38 kg),305 days milk yield (2045.66±531.92 kg)  and lactation length (282.90±49.46 days) were highly significant (p
Keywords: Milk production traits; Service period; Dry period; Gestation period; Kankrej cow